2006
DOI: 10.1080/18811248.2006.9711078
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Microstructure and Microchemistry in Cold-worked 316 Stainless Steels under PWR Irradiation

Abstract: The evolution of microstructures and microchemistry was examined by transmission electron microscopy in coldworked SUS 316 stainless steel components irradiated in a pressurized water reactor to 1-73 dpa at 565-596 K. Homogenous nucleation of dislocation loops, helium bubbles and 0 precipitates was detected. The dislocation loops consisted of a high density of Frank loops and black dots. The black dots are considered to be small Frank loops, some fraction of which could be vacancy-type. The size distribution s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…IASCC susceptibility, mechanical properties and microstructures of the as-irradiated tube materials were thoroughly examined in the previous studies. 4,13,14) It was confirmed that the tube materials were susceptible to IASCC at 4 dpa and highly susceptible at 35 dpa and that the microstructure mainly consisted of dislocation loops with a diameter of $12 nm and dense small bubbles with well-developed grain boundary segregation of Cr, Ni, Si, and Mo.…”
Section: Methodsmentioning
confidence: 59%
See 1 more Smart Citation
“…IASCC susceptibility, mechanical properties and microstructures of the as-irradiated tube materials were thoroughly examined in the previous studies. 4,13,14) It was confirmed that the tube materials were susceptible to IASCC at 4 dpa and highly susceptible at 35 dpa and that the microstructure mainly consisted of dislocation loops with a diameter of $12 nm and dense small bubbles with well-developed grain boundary segregation of Cr, Ni, Si, and Mo.…”
Section: Methodsmentioning
confidence: 59%
“…Time-dependent processes such as hydrogen accumulation were considered. 12,13) The present results suggest another possible explanation in terms of deformation characteristic. As mentioned before, it was confirmed that the twinning was dominant at the faster strain rate in the 35-dpa specimen.…”
Section: Grain Boundary Separationmentioning
confidence: 61%
“…Small voids or 'cavities that could be either voids or bubbles' have also been observed in thin-walled flux thimble tubes removed from various PWRs [42][43][44][45]. A special case of 'sub-visible' voids [45] in one of these flux thimble tubes will be covered later.…”
Section: Review Of Data Supporting the Potential For Void Swelling Inmentioning
confidence: 97%
“…Figure 9 shows a comparison of the dose dependences of material property changes of the same CW316 stainless Step spacing µ Fig. 9 Dose dependence of material properties and border stress for IASCC failure steels examined in the previous studies 9,11) and the border stress for IASCC failure in Fig. 8.…”
Section: Discussionmentioning
confidence: 99%
“…10) IASCC susceptibility, mechanical properties and microstructures of the as-irradiated tube materials were thoroughly examined in the previous studies. [9][10][11] UCL tests were conducted at 320 C in the simulated PWR primary water (500 ppm B, 2 ppm Li, 30 ccH 2 /kgH 2 O). Stress was gradually loaded to the specimens at a fast strain rate of 3:3 Â 10 À4 /s, to avoid specimen fracture due to IASCC during dynamic straining before reaching target applied stresses.…”
Section: à8mentioning
confidence: 99%